Features of the formation of pathogenetic changes of the placental complex on the background of intra-uteronomy infection - Hoshovska, Alisa (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2022)
Abstract. One of the main complications during early embryogenesis and placentation is placental insufficiency. Under the influence of various factors, namely infectious factors, which, depending on the biological specificity, negatively affect the germ cells of the parents, the development of the embryo, the formation of the trophoblast and the placenta, which in turn leads to a violation of the function of the placental complex and gestational complications during pregnancy. Due to the expansion of diagnostic possibilities for detecting placental function disorders, as well as in connection with the emergence of new data on the mechanisms of blood circulation regulation in the placenta to assess the functional state of the feto-placental complex at the stage of the formation of primary placental insufficiency against the background of inflammatory diseases of the female genital organs, we were determined the dopplerometric pattern of blood flow (ovarian artery, intervillous space) in women of the main and control groups. Goal. To determine the dopplerometric pattern of blood flow characteristics (ovarian artery, chorionic volume, blood flow study in different areas of the chorion) in pregnant women against the background of inflammatory diseases of the female genital organs in the early trimester of pregnancy. Materials and methods. The main group consisted of 37 women with signs of inflammatory diseases of the female genital organs, the control group consisted of 30 practically healthy women. The results. Obtaining new data on the mechanisms of blood circulation regulation in the ovarian artery and intervillous space at the stage of formation of the placental complex in physiological and complicated pregnancy will allow to supplement the question of the pathogenesis of the development and prevention of placental insufficiency. Conclusions. The study of the blood flow of extraembryonic structures in the early stages of gestation allows to diagnose structural changes at the stage of placenta formation. Violation of blood flow in the first trimester of pregnancy against the background of an infectious factor that penetrates into various vascular links of the mother-placenta-fetus system with the deduction of blood flow volume indicators demonstrates the regularity of the formation of disturbed hemodynamics at the stage of formation of the placental complex. These indicators can serve as a criterion for the selection of women of the risk group for the formation of primary placental insufficiency.